Low skeletal muscle density combined with muscle dysfunction predicts adverse events after adult cardiovascular surgery. (11th May 2021) - Yamashita, M; Kamiya, K; Matsunaga, A; Kitamura, T; Hamazaki, N; Nozaki, K; Ichikawa, T; Maekawa, E; Meguro, K; Yamaoka-Tojo, M; Miyaji, K
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): This study was supported by the Grant for Japan Society for the Promotion of Science (JSPS) KAKENHI. Introduction: Although muscle dysfunction is widely known as a poor prognostic factor in patients with cardiovascular disease, no study has examined whether the addition of low skeletal muscle density (SMD) assessed by computed tomography (CT) to muscle dysfunction is useful. Purpose: The present study aimed to examine whether SMDs can strengthen the predictive ability of muscle dysfunction for adverse events in patients who underwent cardiovascular surgery. Methods: We retrospectively reviewed 853 patients (median age: 69 years, 65.1% male) aged ≥40 years who had preoperative CT for risk management purposes and muscle dysfunctions measured during postoperative cardiac rehabilitation. Muscle dysfunctions were determined from weakness (low grip strength) and slowness (slow gait speed) based on the Asia Working Group for Sarcopenia. Low SMD based on transverse abdominal CT images was defined as a mean Hounsfield unit of the psoas muscle <45. To examine the complementary prognostic value for all-cause deaths, all-cause events, and cardiovascular-related events when low SMDs were added to four patterns of muscle dysfunction (weakness only, slowness only, weakness or slowness, and weakness and slowness), the continuous net reclassification improvement (cNRI) and integrated discrimination improvement (IDI) index were calculated. Results: For all definitions of muscle dysfunction, the addition of SMDs was shown to significantly improve the cNRI (estimates: 0.377 to 0.468 for all-cause death, 0.220 to 0.248 for all-cause events, 0.308 to 0.322 for cardiovascular-related events) and IDI (estimates: 0.005 to 0.011 for all-cause death, 0.005 to 0.010 for all-cause events, 0.009 to 0.012 for cardiovascular-related events) in all analyses. Low SMDs combined with muscle dysfunctions were associated with the highest risk of all-cause death (Figure 1: A-D). Patients with neither low SMDs nor muscle dysfunction had the lowest risk of all-cause events and cardiovascular-related events (Figure1: E-L). Conclusion: The predictive ability of muscle dysfunction for adverse events was consistently increased by addition of SMDs in patients who underwent cardiovascular surgery. Our results suggest that when CT is performed for any clinical investigation, the addition of the organic assessment of skeletal muscle can strengthen the diagnostic accuracy of muscle wasting.